Pengaruh Pemberian Ransum Mengandung Cacahan Eceng Gondok (Eichhornia crassipes) Kering terhadap Kualitas Karkas dan Non Karkas Entog (Cairina moschata) Jantan - Hildan Septian; Dini Widianingrum; Ulfa Indah Laela Rahmah (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2026)
This research aims to determine the effect of feeding dry water hyacinth (CEGK) on the quality of carcass and non-carcass Muscovy male ducks, as well as determining the appropriate level of CEGK inclusion. The study used a Completely Randomized Design (CRD) with four levels of CEGK inclusion: 0% (control), 5%, 10%, and 15%, each with five replications. The variables observed included live weight, slaughter weight, carcass weight, carcass percentage, weight without feathers, main parts of the carcass (breast, thighs, wings, back), and non-carcass parts (head, neck, feathers, blood, entrails, feet). Ducks are slaughtered at 145 days of age. Analysis of variance (ANOVA) showed that CEGK supplementation had a significant effect (P<0.05) on live weight and weight without feathers, but had no significant effect (P>0.05) on slaughter weight, carcass weight, carcass percentage, main parts of the carcass, or non-carcass parts. The highest live weight was achieved at an inclusion level of 15% (1700 g), followed by 10% (1663 g), while the highest weight without feathers was also at 15% (1555 g). Although live weight is highest at 15%, an inclusion rate of 10% is recommended as it shows better feed efficiency and a relatively higher carcass percentage trend than 15%, thereby providing an optimal balance between growth performance and carcass quality and supporting the economical use of local feed sources.